The Effect of Hedonic Shopping Motivation, Visual Merchandising and Price Discounts on Impulsive Purchases - Annisa, Annisa; Nuvriasari, Audita (Research Horizon, 2024)
This study aims to analyze the influence of Hedonic Shopping Motivation, Visual Merchandising, and Price Discounts on impulsive purchases at Galaxy Beauty Store Yogyakarta. The sampling technique used was purposive sampling with a sample size of 100 consumers from Galaxy Beauty Store Yogyakarta. The data analysis method employed was Multiple Linear Regression analysis. The results of the study indicate that Hedonic Shopping Motivation and Visual Merchandising have a positive and significant effect on impulsive purchases. This means that higher hedonic shopping motivation and better visual merchandising are associated with an increased likelihood of impulsive buying behavior. Conversely, Price Discounts have a negative and significant effect on impulsive purchases, suggesting that discounts may actually reduce the tendency for impulsive buying. This research provides insights into the factors influencing impulsive purchasing behavior and can help in developing marketing strategies for Galaxy Beauty Store Yogyakarta.